Reality Faced by Dental Students during COVID-19 Pandemic Situation - Bhosale, Trupti; Mathew, Roshni; Hegde, Amitha M. (Journal of Health and Allied Sciences NU, 2023)
The COVID-19 pandemic was causing an unfavorable effect on the education and mental health of students. Much information about this virus is available, but its effect on mental health has been overlooked during this pandemic. Also, disruption in the academic year had led to more of virtual learning. The pros and cons of virtual learning need to be assessed, there is a need to evaluate whether there has been a shift in approach toward dental practice.So in our survey, we evaluated the mental health, efficiency of virtual learning, and attitude toward future dental practices among dental students during the COVID-19 pandemic.Objectives The aim of this study was to evaluate the mental health, efficiency of virtual learning, and attitude toward future dental practices among dental students during the COVID-19 pandemic.Materials and Methods In this study, we included 87 final-year dental undergraduate students from A B Shetty Memorial Institute of Dental Sciences (ABSMIDS). The study was conducted through online questionnaire using google link.Results In our survey, we found that many of the student's mental health was affected as they experienced certain level of depression, isolation, and mood swings, which affected their sleeping pattern. So we can consider counseling sessions for the students. We also found that virtual learning is a convenient alternative, but it also has some drawbacks as it caused physical discomforts like eye strain, back pain, etc. The students' responses were overwhelmingly positive with regard to future dental practices, but they felt there is a need to treat patients with protective equipment and guidance.Conclusions Our study showed that this pandemic had hampered the mental health status of students in some ways. Also, it showed that virtual learning is helpful and is a convenient alternative, but it has some drawbacks as it causes physical discomforts. The students' responses were overwhelmingly positive with regard to future dental practices, but they need to treat patients with protective equipment.The Covid pandemic waves had made it difficult to control the situation, which resulted in extended periods of lockdown. Hence, these factors should be considered for the benefit of students in order to manage any future outbreaks in a better way.
Keywords: COVID-19; pandemic; virtual learning; mental health; students; dental practices